The Role of Sulh (Conciliation) for Spritual Advancement in Islam - Muhammathu Mubarak Shiyana; Farhana Mohamed Suhaimi; Abidah Abdul Ghaffar (Faculty of Syariah and Law, USIM, 2026)
This qualitative study aims to explore the spiritual dimensions of sulh in the quran through a doctrinal legal textual analysis technique. The primary data comprises texts from the Quran and Hadith, while the secondary data encompasses plenty of Islamic classical commentaries, journal articles, theses, and online resources. The Qur'an and Sunnah consistently underscore the importance of sulh in various contexts. Sulh is seen as an effective way to settle disagreements instead of resorting to court. This embraces diverse ADR approaches such as mediation, negotiation, and reconciliation. Sulh is presented as a broad moral ideal that is integrated into Islamic ethics and the daily lives of Muslims. Accordingly, the Quran informs believers that Sulh should be framed as a moral duty and a spiritual act that is pleasing to God and encouraged among people. A person can achieve inner peace and spiritual purification by practising divine qualities such as mercy and forgiveness through reconciliation. Therefore, this study concludes that using the approach of Sulh can be an effective way to implement Islamic ideals founded on peace and spiritual purification and to gain closeness to God. This study contributes a profound theoretical understanding of reconciliation in Islamic thought. The researchers suggest a further investigation into broader religious dimensions of sulh within the Islamic system.